High-Protein Energy-Restriction: Effects on Body Composition, Contractile Properties, Mood, and Sleep in Active Young College Students - Roth, Christian; Rettenmaier, Lukas; Behringer, Michael (Frontiers in Sports and Active Living, 2021)
Athletes are often advised to ensure a high protein intake during energy-restricted diets. However, it is unclear whether a high protein intake is able to maintain muscle mass and contractility in absence of resistance training. After 1 week of weight maintenance (45kcal/kg), 28 male college athletes not performing resistance training were randomized to either the energy-restricted (ER, 30kcal/kg, n=14) or the eucaloric control group (CG, 45kcal/kg, n=14) for 6 weeks. Both groups had their protein intake matched at 2.8g/kg/FFM and continued their habitual training throughout the study. Body composition was assessed weekly using multifrequency bioelectrical impedance analysis. Contractile properties were examined with Tensiomyography and MyotonPRO at pre, mid, and post, along with sleep (PSQI) and mood (POMS). ER revealed a significant decline in body mass, lean body mass, body cell mass, intracellular water and body fat compared to the CG (p < .05). While contractile properties did not change (p > .05), PSQI score and vigor decreased significantly in both groups (p < .05). The present data show that a high-protein intake alone was not able to prevent lean mass loss associated with a 6-week moderate energy restriction in college athletes. However, muscle contractility was not negatively altered by this form of energy restriction. Whether this advantage is due to the high protein intake cannot be clarified with the present study and warrants further study. In summary, decreasing energy intake moderately while increasing protein consumption does not maintain lean body mass but contractility in absence of resistance training in male college athletes. The study was approved by the local ethics committee (#2019-24, Goethe University Frankfurt, GER) and was conducted in accordance with the ethical standards set by the declaration of Helsinki. Moreover, the study was preregistered in the International Clinical Trials Registry Platform (WHO) with the registration number DRKS00017263.